Patient-specific access planning in minimally invasive mitral valve surgery. (March 2020) - Di Perna, Dario; Castro, Miguel; Gasc, Yannig; Haigron, Pascal; Verhoye, Jean-Philippe; Anselmi, Amedeo
Abstract: Background: Minimally invasive mitral valve repair or replacement (MIMVR) approaches have been increasingly adopted for the treatment of mitral regurgitation, allowing a shorter recovery time and improving postoperative quality of life. However, inadequate positioning of the right mini thoracotomy access (working port) translates into suboptimal exposure, prolonged operative times and, potentially, reduction in the quality of mitral repair. At present, we are missing tools to further improve the positioning of the working port in order to ameliorate surgical exposure in a patient- specific fashion. Methods and evaluation of the hypothesis: We hypothesized that computation of relevant anatomical measurements from preoperative CT scans in patients undergoing MIMVR may provide patient-specific information in order to propose the surgical access that best fits to the patient's morphology. We hypothesized that this may systematize optimal mitral valve exposure, facilitating the procedure and potentially ameliorating the outcomes. We also hypothesized that preoperative simulation of the working port site and surgical instruments' insertion using a three-dimensional virtual model of the patient is feasible and may help in the customization of ports positioning. The hypothesis was evaluated by a multidisciplinary team including cardiac surgeons, experts in medical image processing and biomedical engineers. CT scans of 14 patients undergoing MIMVR were segmented to visualize 3D chest bones and heart structures meshes. The mitral valve annulus is pointed manually by the expert or extracted automatically when contrast-enhanced CT scan was available. The valve plane was then calculated and the optimal incision location analyzed according to a) the perpendicularity and b) the distance between the intercostal spaces and the valve plane. An angle-chart representation for the 4th, 5th and 6th intercostal spaces and a color map illustrating the distance between the skin and the mitral valve were created. We started the development of a simulation tool for preoperative planning using 3D Slicer software. Conclusions: Several patient-specific factors (including the orientation of the mitral valve plane and the morphology of the chest cage) may influence the performance of a MIMVR procedure, but they are not quantitatively considered in the current planning strategy. We suggest that the clinical results of MIMVR can be improved through preoperative virtual simulation and computer-assisted surgery (through determination of working port and surgical instruments insertion positioning). Further research is justified and the development of a software tool for clinical evaluation is warranted to verify the current hypothesis.